Staphylococcus aureus nasopharyngeal carriage in rural and urban northern Vietnam. - Van Nguyen, K; Zhang, T; Thi Vu, B; Dao, T; Tran, T; Thi Nguyen, D; Thi Tran, H; Thi Nguyen, C; Fox, A; Horby, P; Wertheim, H (2014)
BACKGROUND: Staphylococcus aureus is a common human pathogen that can colonise the respiratory tract and cause infection. Here we investigate the risk factors associated with nasopharyngeal carriage of S. aureus (including methicillin-resistant S. aureus [MRSA]) in Vietnam. METHODS: Between February and June 2012, nasal and pharyngeal swabs for S. aureus culture, and demographic and socioeconomic data were taken from 1016 participants in urban and rural northern Vietnam, who were randomly selected from pre-specified age strata. RESULTS: Overall S. aureus prevalence was 303/1016 (29.8%; adjusted for age: 33.8%). Carriage in the main cohort was found to be associated with younger age (≤5 years [OR 3.13, CI 1.62-6.03]; 6-12 [OR 6.87, CI 3.95-11.94]; 13-19 [OR 6.47, CI 3.56-11.74]; 20-29 [OR 4.73, CI 2.40-9.31]; 30-59 [OR 1.74, CI 1.04-2.92); with ≥60 as reference), living in an urban area (OR 1.36, CI 1.01-1.83) and antibiotics use (OR 0.69, CI 0.49-0.96). MRSA was detected in 80/1016 (7.9%). Being aged ≤5 years (OR 4.84, CI 1.47-15.97); 6-12 (OR 10.21, CI 3.54-29.50); 20-29 (OR 4.01, CI 1.09-14.77) and wealth (>3/5 wealth index, OR 1.63 CI 1.01-2.62) were significant risk factors for MRSA carriage. CONCLUSIONS: Nasopharyngeal carriage of S. aureus is present in one-third of the Vietnamese population, and is more prevalent among children. Pharyngeal carriage is more common than nasal carriage. Risk factors for S. aureus (including MRSA) carriage are identified in the community.